Rezension von: Sauer, Willi; Kootz, Wolfgang, Schwäbisch Hall - Wunder, Gerd (Württembergisch Franken, 1979)
Schwäbisch Hall. Stadtführer. Willi Sauer / Wolfgang Kootz. 60 S. 50 (farbige) Abb. Heidelberg: E.v. König. 1978.